EDUKASI DAN PELATIHAN PEMBUATAN HANDWASH DARI AMPAS TEH DI SMK MUHAMMADIYAH LARANGAN - Purgiyanti Purgiyanti; Meliyana Perwitasari; Dwi Ayuningtyas; Aldi Budi Riyanta; Tri Adjeng; Dyah Ayu (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Tea that has been brewed leaves a residue or residue which we know as tea dregs. Natural ingredients which contain many bioactive compounds that can be used as antiseptics and antibacterials are found in these tea dregs. One preparation that can be made by utilizing natural compounds from tea dregs is handwash. This preparation is a preparation that is used as a hand wash to obtain maximum hand hygiene after cleaning the hands. The aim of this service activity is to provide education and skills in making handwash from tea dregs. Tea dregs are used as an effort to make greater use of residual natural materials (waste) so that they can be of maximum benefit in processing them. The method used in this activity is socialization, approach and practice in making handwash. The target of this activity is students of SMK Muhammadiyah Larangan Brebes. The result of this PKM is that education and training has been carried out on making handwash using tea dregs. This activity, which was attended by 199 students and 7 teachers, is expected to increase knowledge and skills specially making handwash preparations from tea dregs